Dietary xylo‐oligosaccharide ameliorates colonic mucus microbiota penetration with restored autophagy in interleukin‐10 gene–deficient mice. Issue 5 (29th October 2021) - Chen, Zhongxia; Shen, Xiao; Zhou, Qunyan; Zhan, Qiang; Xu, Xingwen; Chen, Qiuyu; An, Fangmei; Sun, Jing
Abstract: Background: Inflammatory bowel disease (IBD) is, nowadays, highly prevalent and presents a global clinical challenge. The objective of this study is to assess the effects of xylo‐oligosaccharide (XOS) on Il10 –/– mice, a classic animal model of IBD. Methods: Male wild‐type (WT) mice were assigned to WT group, and Il10 –/– mice were assigned to interleukin‐10 gene–deficient (IL‐10–KO) group and XOS group, respectively. There were 6–8 mice aged 8 weeks in each group. Mice in the XOS group received 1.0 g/kg/day XOS by gavage for 4 weeks. Results: Compared with mice in IL‐10–KO group, Il10 –/– mice with XOS intervention presented significant mild spontaneous colitis with lower disease activity index, histological scores, and bowel inflammatory cytokine levels. Dietary XOS downregulated bowel mucus bacterial penetration, which occurred as early as the onset of bowel colitis. The effect of XOS was associated with restored expression of LC3II/I and decreased expression of p62 and beclin‐1 in colon. Conclusions: Therefore, XOS decreases colonic mucus microbiota penetration with restored function of antophagy. Our findings suggest that XOS may be a potential dietary supplement or functional food for early management of IBD.